Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Beban Kerja terhadap Kinerja Karyawan - Yuan Badrianto; Muhamad Ekhsan; Cucu Mulyati (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This research is motivated by problems in the Company related to leadership style that does not help employees to be motivated, maintain and increase motivation within themselves. The employee's work environment needs to have sufficient facilities to support daily work in order to improve performance, and a high workload that is sometimes beyond the ability of employees. The purpose of this study was to analyze the effect of leadership style, work environment and workload on the performance of employees of PT. NFI is part of the fillpack. This study uses quantitative research methods. The data analysis method used is validity test, reliability test, normality test, linearity test and regression coefficient (hypothesis). The population of this research is the employees of PT. NFI part of the fillpack as many as 130 employees. This study uses a probability sampling method with a simple random sampling technique, meaning that all members of the population are assumed to have the same opportunity to be selected as the research sample. The results of the study which were processed using the SPSS version 22 for windows program in the t-test (partial) showed that leadership style significantly affected employee performance with a t-count value of 2.886 > t-table 1.989, the influence of the work environment significantly affected employee performance with a t-count value 2,276 > t table 1,989 and the workload also significantly affects employee performance with a t count value of 2,183 > t table 1,989. Thus the researcher can conclude that the variables of leadership style, work environment and workload can be considered and used as benchmarks in employee performance.